Research of fresh/salt water in Upper-middle Pleistocene (qp2–3) in Bac Lieu Province - Trinh, Hoai Thu; Tran, Thi Thuy Huong; Pham, Ba Quyen; Le, Duc Anh; Mai, Duc Dong; Nguyen, Manh Khai; Tran, Thi Minh Hang; Nguyen, Huyen Trang (Vietnam Journal of Marine Science and Technology, 2024)
This study identified the relationship between Total Dissolved Solids (TDS) and Electrical Conductivity (EC) with the TDS = 0.6628*EC = 0.1706 correlation, in which the correlation coefficient is r = 0.984 and the Standard Error (±%) is 2.78%. The TDS content is determined by small relative error and a high correlation coefficient of the conductivity, which applies to calculate the TDS content of other groundwater samples in Bac Lieu Province. Also, the temperature difference in the electrical conductivity measurement affects the TDS content; thus, the study has determined that the temperature compensated constant between the electrical conductivity on the field and those at 25oC is 0.002953. According to the data and the analysis of the TDS content, the fresh-salt water distribution map of the qp2–3 aquifers has been established, and its boundary has been more detailed and standardized than in the previous study. In particular, TDS values range from 0.437 g/L to 2.0 g/L. The areas that contain brackish and salt water are distributed discontinuously, forming the saline zones in Loc Ninh, Phuoc Long communes in Hong Dan district; Phuoc Long, Hung Phu communes in Phuoc Long district; Vinh Hau, Vinh Binh communes in Hoa Binh district, and Thuan Hoa commune in Bac Lieu city. The saltwater area of the qp2–3 aquifers is about 398 km2, accounting for 16% of the study’s total area. The results fresh-salt water distributed mapping provide the environmental management institution with a comprehensive view of the distribution of fresh-salt water to propose effective groundwater exploitation policies.